Case Report: High-Calorie Glucose Infusion and Tight Glycemic Control in Ameliorating Refractory Acidosis of Empagliflozin-Induced Euglycemic Diabetic Ketoacidosis - Wan Azman, Siti Sanaa; Sukor, Norlela; Abu Shamsi, Muhammad Yusuf; Ismail, Ilham; Kamaruddin, Nor Azmi (Frontiers in Endocrinology, 2022)
The current widespread use of sodium-glucose co-transporter 2 (SGLT2) inhibitors has triggered an increase in reported cases of euglycemic diabetic ketoacidosis (EDKA), often characterized by a protracted metabolic acidosis that is resistant to conventional DKA treatment. We report a case of empagliflozin-induced EDKA with severe metabolic acidosis intractable to aggressive fluid resuscitation and boluses of bicarbonate infusion. Following the introduction of high-calorie glucose infusion coupled with tight glycemic control, the recalcitrant acidosis was successfully corrected. This is the first case report that adopts the above approach, representing a paradigm shift in the management of SGLT2 inhibitor-induced EDKA.